2007
DOI: 10.1517/14656566.8.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the inhibitor of ADAMTS13 in thrombotic thrombocytopenic purpura

Abstract: There has clearly been an evolution in the treatment of thrombotic thrombocytopenic purpura (TTP) over the past several years based upon a better understanding of the pathophysiology of this disorder. An autoantibody inhibitor of the ADAMTS13 protease and the resulting severe deficiency of ADAMTS13 function seem to be significant risk factors for the development of TTP, a disease increasingly recognized as an autoimmune disorder. Immune-based therapy aimed at suppressing the inhibitor of ADAMTS13 has been appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
(33 reference statements)
2
7
0
Order By: Relevance
“…In agreement with previous reports, 17,18,28 the data suggest that most cases of acquired TTP presented with excess amounts of ADAMTS13 inhibitor that cannot be eliminated effectively in a few days of PE therapy. Clinicians should make effort to order ADAMTS13 work-up on the pretreatment samples to obtain a more reliable laboratory result.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous reports, 17,18,28 the data suggest that most cases of acquired TTP presented with excess amounts of ADAMTS13 inhibitor that cannot be eliminated effectively in a few days of PE therapy. Clinicians should make effort to order ADAMTS13 work-up on the pretreatment samples to obtain a more reliable laboratory result.…”
Section: Discussionsupporting
confidence: 92%
“…The data from our study demonstrated that in more than 78% (14/18) of the cases, the samples taken prior PE Procedure 4 correctly classify patients for diagnosis of TTP. In agreement with previous reports, the data suggest that most cases of acquired TTP presented with excess amounts of ADAMTS13 inhibitor that cannot be eliminated effectively in a few days of PE therapy. Clinicians should make effort to order ADAMTS13 work‐up on the pretreatment samples to obtain a more reliable laboratory result.…”
Section: Discussionsupporting
confidence: 92%
“…All patients responded to treatment. Median time to response after the first dose of rituximab was 10 days (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). In particular, the achievement of a platelet count higher than 100.00/lL and a near to full normalization of hemolytic parameters, were observed in 2, 1 and 1 patients after the first, second and third weekly doses of rituximab, respectively.…”
mentioning
confidence: 99%
“…In particular, the achievement of a platelet count higher than 100.00/lL and a near to full normalization of hemolytic parameters, were observed in 2, 1 and 1 patients after the first, second and third weekly doses of rituximab, respectively. To date, all the patients are well and active, being free of TTP relapse after a median follow-up of 10 months (4)(5)(6)(7)(8)(9)(10)(11)(12). Recent advances in our understanding of idiopathic TTP have provided a rationale for the use of rituximab to achieve an effective B-cell depletion and clinical improvement in acute autoimmune TTP [2,8,9], which is attributed to the production of anti-ADAMTS13 autoantibodies.…”
mentioning
confidence: 99%
See 1 more Smart Citation